Persistent High-Risk HPV Infection and Molecular Changes Related to the Development of Cervical Cancer - Pablo Moreno-Acosta; Alfredo Romero-Rojas; Nicolas Vial; Antonio Huertas; Jinneth Acosta; Diana Mayorga; Schyrly Carrillo; Monica Molano; Oscar Gamboa; Martha Cotes; Camila Casadiego; Alexis Vallard; et al. (Hindawi Limited, 2020)
This article is a preliminary investigational study that is aimed at giving hints about the interesting biomarkers involved in the transition process from low-grade cervix lesion to invasive cervical cancer. Our study focuses on the risk factors and tumour molecular changes in one patient. First in 1986, she was diagnosed a preinvasive cervix lesion. Then, 16 years later, she was diagnosed an invasive cervical cancer. The 2002 diagnosis was a squamous cell carcinoma of the cervix, stage IIIB (FIGO), whereas in 1986, she had been diagnosed a high-grade squamous intraepithelial cervical lesion. Retrospectively, the analysis of samples of preneoplastic lesions and invasive cervical cancer confirmed the histopathological diagnoses and detected the presence of HPV type and HPV-16 variants, as well as the overexpression of proteins such as hTERT, IGF1Rα, IGF1Rβ, CAIX, and GLUT1. Finally, the Arg72Pro polymorphism was detected in TP53. The role of high-risk HPV and HPV-16 variants and of hTERT, IGF1Rα, IGF1Rβ, CAIX, and GLUT1 variations seemed confirmed in the development and progression of cervical cancer. As a result, analyzing the molecular changes in one and same tumour that progresses from a low-grade cervix lesion to invasive cervical cancer could provide valuable information in order to improve detection, diagnosis, and treatment in the future.